Secretory mechanisms for the male produced aggregation pheromone of the palm weevil Rhynchophorus palmarum L. (Coleoptera: Curculionidae) - Sánchez, P.; Cerda, H.; Cabrera, A.; Caetano, F. H.; Materán, M.; Sánchez, F.; Jaffé, K. (Elsevier, 1996)
Histological and chemical analyses of different corporal segments of the palm weevil Rhynchophorus palmarum, revealed the presence of two symmetrical glands (modified salivary glands) in the prothorax of males, but absent in females. Using gas chromatography and mass sepectrometry, we demonstrated the presence of rhynchophorol (aggregation pheromone) in extracts of this gland, as well as in the rostrum and digestive tract (rectum) of males. Olfactometric experiments showed that the release of the aggregation pheromone starts approximately 10 min after the insect detects ethyl-acetate and continues for several hours. The pheromone is secreted through the feces and more concentrated through the mouth to a depression on the dorsal part of the rostrum where, via hairs and the surface tension of the secretion, it collects in a complex structure consisting of various types of hairs, which help disperse the pheromone.
Keywords: Gland Aggregation; Pheromone; Rhynchophorus palmarum; Secretory mechanism